Abnormal bone histology in idiopathic hypercalciuria - Malluche, H H; Tschoepe, W; Ritz, E; Meyer-Sabellek, W; Massry, S G (The journal of clinical endocrinology and metabolism, 1980)
Bone histology was evaluated in iliac creast biopsies of 15 patients with idiopathic hypercalciuria of the hyperabsorptive type and recurrent calcium oxalate stone formation. The biopsies were studied using quantitative histomorphometric analysis of undecalcified sections and fluorescent microscopy after double tetracycline labeling. Uring calcium and cAMP excretion were measured under basal conditions and after oral administration of calcium phosphate. Absorptive hypercalciuria was defined as a urinary excretion of calcium of more than 15 meq/24 h and/or a urinary ratio of Ca to Cr of more than 0.2, with a fall in the Ca to Cr ratio of more than 40% after the administration of oral cellulose phosphate. Osteoclastic bone resorption was normal or low in all patients and did not show any recognizable correlation with urinary calcium or urinary cAMP. All but one of the patients showed an increase in the fraction of inactive osteoid. Total osteoid was increased in 60% of the patients. Osteoblastic activity was significantly lower in the patient than in the control subjects. The fraction of mineralizing osteoid seams (i.e. seams with a tetracycline double labeling pattern), was diminished in all patients and the mean rate of apposition of bone matrix was decreased. These findings point to a diminished amount of bone matrix produced by individual osteoblasts and to a delay or cessation of terminal (secondary) mineralization of osteoid seams.